2015
DOI: 10.1039/c5ra05604g
|View full text |Cite
|
Sign up to set email alerts
|

The importance of Au⋯π(aryl) interactions in the formation of spherical aggregates in binuclear phosphane gold(i) complexes of a bipodal thiocarbamate dianion: a combined crystallographic and computational study, and anti-microbial activity

Abstract: Compact molecular structures of antimicrobial (R3PAu)2L (R = Et (1), Ph ((2) and Cy ((3); LH2 = {1,4-[MeOC(S)-N(H)]2C6H4}), arise from intramolecular Au⋯π(aryl) interactions, proven by theory to be attractive and 12 kcal mol–1 more stable than anticipated Au⋯O interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…Au···O or Au···π(aryl), decreased with a concomitant increased deviation of the P-Au-S angle from linearity. The observation of the greater distortion of the P-Au-S angle in the structures with the Au···π(aryl) interaction is consistent with the notion that this is more significant than the Au···O interaction [11]. This conclusion is substantiated by further calculations indicating the conformer with the Au···π(aryl) interaction is more stable by 5.2 kcal/mol than the one with the Au···O contact.…”
Section: Molecular Structure: Theoreticalsupporting
confidence: 77%
See 3 more Smart Citations
“…Au···O or Au···π(aryl), decreased with a concomitant increased deviation of the P-Au-S angle from linearity. The observation of the greater distortion of the P-Au-S angle in the structures with the Au···π(aryl) interaction is consistent with the notion that this is more significant than the Au···O interaction [11]. This conclusion is substantiated by further calculations indicating the conformer with the Au···π(aryl) interaction is more stable by 5.2 kcal/mol than the one with the Au···O contact.…”
Section: Molecular Structure: Theoreticalsupporting
confidence: 77%
“…Therefore, it was of interest to evaluate the energetics/relative importance of the Au···O/Au···π(aryl) interactions in the conformational polymorphs of (I). This was accomplished by employing similar theoretical methods and basis sets reported recently for binuclear gold molecules with related bipodal ligand which also featured intramolecular Au···π(aryl) interactions [11] and for systems having aurophilic interactions [33]. Energy minimization calculations showed that there are two stable conformers each corresponding to an experimental structure and related by a torsion motion around the C-S bond.…”
Section: Molecular Structure: Theoreticalmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of the former, anions that are derived from thiocarbamates complex phosphanegold(I) species to form molecules of the general formula R″3PAu[SC(OR)=NR′] (R, R′, R″ = alkyl, aryl), compounds that exhibit anti-cancer potential [1] and bactericidal properties [2]. Crystals of these species are often forthcoming enabling the evaluation of systematic variations of the R, R′, and R″ substituents upon the molecular packing and solid-state luminescence [3,4]. Indeed, the uncoordinated molecules are also of interest, as they, too exhibit varied supramolecular association depending on aryl-bound substituents [5,6], especially in circumstances when the nitrogen-bound groups carry pyridyl functionality [7].…”
Section: Introductionmentioning
confidence: 99%